Sessile serrated adenomas detection rate among the surgeons and the gastroenterologists: A retrospective analysis - Devisha Raina; Rasika Hendahewa (Eastern Journal of Medical Sciences, 2021)
Background: Sessile serrated adenomas (SSAs) are flat or sessile benign lesions occasionally covered by a mucous cap and invariably lead to colorectal cancer. The adenoma detection rate (ADR) is recognized as an important quality measure for colonoscopy. Objective: The objective of the study was to evaluate and compare the ADR during colonoscopy among surgeons and gastroenterologists. Materials and Methods: In this retrospective analysis, all colonoscopies performed during July 2018–July 2019 at Caboolture Hospital, Queensland, Australia were included in the study. After considering the inclusion and exclusion criteria, the rate of sessile polyp detection among the gastroenterologist versus surgeons was investigated by calculating a correlation coefficient weighted by factors such as experience, colonoscopy intubation time, and removal of scopes. Results: A total of 3425 colonoscopies performed by 7 surgeons and 4 gastroenterologists were assessed. Among them, 58.7% colonoscopies were performed by the surgeons, while gastroenterologists performed 41.3% colonoscopies. The median age of patients was 56.5 years (25–88 years), more common in male than female (58.9% and 41.1%, respectively, p<0.0001). The average withdrawal time among the surgeons and gastroenterologist was 8.05 and 8.54 min, respectively (p=0.02). Mean cecal intubation rate among the surgeons and gastroenterologist was 94.7% and 97.4%, respectively. Most patients had adequate bowel preparations; however, poor bowel preparation was observed among 6.15% gastroenterology patients and 5.6% in surgical patients. Conclusion: Based on the longer withdrawal time and improved skillset, sessile serrated polyp detection rate during colonoscopy was higher among the gastroenterologist as compared to the surgeons.